Analysis of errors in English predication structures in the written work of the Grade V and VI pupils of Francisco Benitez Elementary School, Manila - Rionda, Carolina San Agustin 1936- ([Quezon City s.n.], 1967)
This study analyzed the errors in English predication structures which frequently occur in pupils' written works in order to trace their possible causes.
Thesis (M.Ed.)--University of the Philippines
Keywords: English language -- Idioms, corrections, errors; English language -- Study and teaching